P-36 Introducing a palliative care simulation day for final year medical students. (20th March 2022) - Taylor, Amy; Doherty, Catherine; Stone, Carol
Abstract : Background: Simulation-based medical education recreates challenging end-of-life scenarios to teach key palliative medicine skills, enhance patient safety and promote participant psychological safety. A palliative medicine week for Queen's University Belfast final year medical students was designed to support application of the palliative medicine undergraduate curriculum, incorporating blended learning of communication skills, simulation, and clinical immersion. Methods: A multidisciplinary teaching faculty of consultants, registrars and specialist nurses developed four simulation scenarios on opioid toxicity, breathlessness, constipation, and agitation. Learning outcomes were mapped to Outcomes for Graduates (General Medical Council, 2018) and the Palliative Medicine Curriculum for Undergraduate Medical Education (Association for Palliative Medicine, 2014). Facilitators received simulation instruction and ran practice sessions with volunteer simulation staff and students. Each scenario includes a debrief and opportunity for repeat simulation, reinforcing skills and boosting confidence. The simulation session is delivered using high quality manikins on simulated wards and contemporaneous feedback is collated. Results: Expert advice, scenario practice and volunteer feedback enhanced scenario development, identifying a key focus for each, therefore spotlighting main learning outcomes and maximising impact. Early qualitative feedback has been unanimously positive. Students identified that scenario complexity and novelty increased value and engagement. Students felt facilitators were supportive, the feedback mechanism was safe, and multidisciplinary input added benefit. Facilitators found the students enthused and engaged. The opportunity to repeat challenging simulations saw students develop confidence and skill in palliative care competencies. Conclusions: Expert advice and trialling scenarios enhance simulation development and promote alignment with student expectations and priorities. Facilitator training, especially debriefing, and opportunities to repeat simulations maximise the learning experience and may be particularly important in palliative care simulation. A multidisciplinary approach highlights the significance of effective interprofessional competency and collaboration. Feedback is crucial in enriching the quality of palliative care simulation in education. References: Association for Palliative Medicine (2014, February). Association for Palliative Medicine curriculum for undergraduate medical education. https://www.apmuesif.phpc.cam.ac.uk/apm-curriculum/ General Medical Council (2018, June). Outcomes for Graduates. https://www.gmc-uk.org/education/standards-guidance-and-curricula/standards-and-outcomes/outcomes-for-graduates/outcomes-for-graduates